Research problems in S-2 theses - Nirwanto, Rahmadi (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2011)
The study is intended to identify, classify, evaluate, describe, and explain the quality and the patterns of research problems in the S-2 theses of the English Education Program at Islamic University of Malang. Qualitative approach and evaluation designs were used. The data of the study were 135 of S-2 theses of the English Education Program at Islamic University of Malang from 2003-2008. The study reveals that the majority of the research problems, as written in the theses, indicate clarity, researchability, variables being involved, areas, designs, non-factual data or information, and significance.